2005
DOI: 10.1115/1.2346703
|View full text |Cite
|
Sign up to set email alerts
|

A New Stall-Onset Criterion for Low Speed Dynamic-Stall

Abstract: The Beddoes/Leishman dynamic-stall model has become one of the most popular for the provision of unsteady aerofoil data embedded in much larger codes. The underlying modelling philosophy was that it should be based on the best understanding, or description, of the associated physical phenomena. Even although the model was guided by the flow physics, it requires significant empirical inputs in the formThese conditions are normally associated with pitching and plunging motions and were initially of much interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 10 publications
(9 reference statements)
4
50
0
1
Order By: Relevance
“…. 12 5 Present experimental conditions overlayed on a lift curve hysteresis loop taken from experiments conducted by Sheng et al [3][4][5]. The experimental conditions are similar to those used in the present study.…”
Section: List Of Figuresmentioning
confidence: 83%
See 2 more Smart Citations
“…. 12 5 Present experimental conditions overlayed on a lift curve hysteresis loop taken from experiments conducted by Sheng et al [3][4][5]. The experimental conditions are similar to those used in the present study.…”
Section: List Of Figuresmentioning
confidence: 83%
“…Note that several different types of airfoil are considered. [5][6][7][8][9][10][11][12][13][14][15] The present experimental conditions are indicated in Figure 6 and Table 1, along with a selection of other relevant experiments reported in the literature. It is evident that while realistic conditions are not quite matched, the present experimental conditions are not unusual.…”
Section: B Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(pitchingdown:20.43 ) that the Cp of upper surface is obviously increased. The Cp value of upper surface is even larger than the value of lower surface at the point about 0.7 times chord.…”
mentioning
confidence: 96%
“…In a series of ramp-up dynamic experiments by the University of Glasgow, Sheng, Galbraith and Coton found that the original Leishman-Beddoes algorithm predicts the dynamic stall vortex formation ahead of the actual situation when the Mach number is 0.12 [24,25]. Then, Sheng et al proposed a new dynamic stall criterion in the original Leishman-Beddoes framework in a low Mach number situation (Ma < 0.3).…”
Section: Modelingmentioning
confidence: 99%